Evaluation of low-dose rituximab for the retreatment of patients with active rheumatoid arthritis: a non-inferiority randomised controlled trial. Issue 8 (30th May 2013) - Mariette, Xavier; Rouanet, Stephanie; Sibilia, Jean; Combe, Bernard; Le Loët, Xavier; Tebib, Jacques; Jourdan, Rosemary; Dougados, Maxime
Abstract : Background: The licensed dose of rituximab in rheumatoid arthritis (RA) is two doses of 1000 mg given 2 weeks apart. A lower dose has never been specifically studied in patients with an inadequate response to anti-tumour necrosis factor (TNF) agents. Objective: To compare the efficacy and safety of rituximab repeat treatment with two doses (1000 mg×1 and 1000 mg×2) following initial treatment with 1000 mg×2. Methods: We set up an open-label, prospective, multicentre, non-inferiority study comprising a non-controlled period (24 weeks) followed by a randomised controlled period (weeks 24–104) in patients with RA and an inadequate response to anti-TNF agents. All patients received one course of rituximab (1000 mg×2) with methotrexate. At week 24, patients achieving a EULAR response (moderate or good) were randomised to rituximab retreatment at 1000 mg×1 (Arm A) or 1000 mg×2 (Arm B). The primary objective measure was disease activity in 28 joints C-reactive protein (DAS28-CRP) area under the curve (AUC) over 104 weeks with a non-inferiority margin defined by 20% (444) of the mean DAS28-CRP AUC (mean±SD 2218±967) of the reference data. Results: The intent-to-treat and per-protocol (PP) populations comprised 143 (A/B: 70/73) and 100 (A/B: 51/49) patients, respectively. The adjusted mean difference in DAS28-CRP AUC (PP) was 51.4 (95% CI −131.2 to 234), demonstrating non-inferiority between arms A and B. The overall rituximab safety profile was similar with both retreatment regimens. Conclusions: Following a clinical response to a first course of rituximab in RA at the licensed dose of 1000 mg×2, retreatment with rituximab at 1000 mg×1 results in efficacy outcomes that are non-inferior to those achieved with retreatment at 1000 mg×2. ClinicalTrials.gov registration number: NCT01126541.